2013
DOI: 10.3846/1648715x.2013.787128
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Critical Success Factors for Construction Projects – An Empirical Study in Lithuania

Abstract: This paper aims to identify a comprehensive list of critical success factors for construction projects in Lithuania. Based on the available literature review, this paper identified 71 success factors under 7 broad groups. Based on the survey results, ten factors including project manager competence, project management team members' competence, project manager coordinating skills, client clear and precise goals/objectives, project value, project management team members' relevant past experience, project manager… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
67
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(71 citation statements)
references
References 31 publications
2
67
0
2
Order By: Relevance
“…Once the data were prepared in a suitable form for the statistical package used, the next step of the research process adopted in this study was the analysis of the data. This study aimed to prioritise the identified drivers and barriers of SC in Cambodia according to their importance, using the RII method [48,49]. For each driver and barrier, the RII was calculated using Equation (1):…”
Section: Discussionmentioning
confidence: 99%
“…Once the data were prepared in a suitable form for the statistical package used, the next step of the research process adopted in this study was the analysis of the data. This study aimed to prioritise the identified drivers and barriers of SC in Cambodia according to their importance, using the RII method [48,49]. For each driver and barrier, the RII was calculated using Equation (1):…”
Section: Discussionmentioning
confidence: 99%
“…Devising effective plans to increase productivity has remained a priority for the construction industry (Dainty & Loosemore 2013). In this context, many research studies have been conducted recently to ascertain the main determinants of productivity in a wide range of countries (Durdyev & Mbachu 2011;Ghoddousi & Hosseini 2012;Gudienė, Banaitis & Banaitienė 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Disertacijos tema paskelbti šeši moksliniai straipsniai: du -žurnaluose, įtrauk-tuose į Thomson Reuters ISI Web of Science sąrašą Gudienė et al 2014), vienas -recenzuojamame užsienio mokslo žurnale (Gudienė, Banaitis 2014), vienas -konferencijų straipsnių rinkinyje, referuotame Thomson Reuters ISI duomenų bazėje (Gudiene et al 2013), vienas -tarptautinės konfe- …”
Section: Darbo Rezultatų Aprobavimasunclassified
“…Išskirta dešimt lemiamų sėkmės veiksnių, labiausiai veikiančių Lietuvos statybos projektų įgyvendinimo sėkmę bei atlikta jų analizė. Skyriaus tematika paskelbti trys straipsniai Gudienė et al 2014;Gudienė, Banaitis 2014).…”
Section: Statybos Projektų įGyvendinimą Lemiančių Sėkmės Veiksnių Dauunclassified